2016
DOI: 10.1158/0008-5472.can-15-1410
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Allele CYP3A7*1C Associates with Adverse Outcomes in Chronic Lymphocytic Leukemia, Breast, and Lung Cancer

Abstract: CYP3A enzymes metabolize endogenous hormones and chemotherapeutic agents used to treat cancer, thereby potentially affecting drug effectiveness. Here, we refined the genetic basis underlying the functional effects of a CYP3A haplotype on urinary estrone glucuronide (E1G) levels and tested for an association between CYP3A genotype and outcome in patients with chronic lymphocytic leukemia (CLL), breast, or lung cancers. The most significantly associated SNP was rs45446698, an SNP that tags the CYP3A7 Ã 1C allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…The CYP3A7 gene is part of the cytochrome P450 family 3 subfamily A gene cluster, which encodes enzymes responsible for the metabolism of multiple and diverse endogenous and exogenous molecules (48), and SNP rs45446698 tags a haplotype of 7 highly correlated variants in the CYP3A7 promoter, known as the CYP3A7*1C allele (49,50). The CYP3A7 gene is predominantly expressed in fetal development, but CYP3A7*1C results in expression in adult carriers (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…The CYP3A7 gene is part of the cytochrome P450 family 3 subfamily A gene cluster, which encodes enzymes responsible for the metabolism of multiple and diverse endogenous and exogenous molecules (48), and SNP rs45446698 tags a haplotype of 7 highly correlated variants in the CYP3A7 promoter, known as the CYP3A7*1C allele (49,50). The CYP3A7 gene is predominantly expressed in fetal development, but CYP3A7*1C results in expression in adult carriers (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…(234.8 6 123.1 pmol/mg microsomal protein, mean 6 S.D., n = 54) (Leeder et al, 2005), the CYP3A7 protein was detected in approximately one of 10 adult livers (n = 59), amounting to 24-90 pmol/mg of microsomal protein (Sim et al, 2005). Recent studies have increasingly showed that gene variances of CYP3A7 are associated with various clinical outcomes, including bone mineral density in postmenopausal women independent of serum levels of dehydroepiandrosterone sulfate (Bácsi et al, 2007); decreased dehydroepiandrosterone sulfate levels in women with polycystic ovary syndrome (Goodarzi et al, 2008); adverse outcomes in chronic lymphocytic leukemia, breast, and lung cancer (Johnson et al, 2016); reduced levels of 2-hydroxylation pathway estrogen metabolites (Sood et al, 2017); and maternal determinants of fetal growth independent of fetal genetics (Beaumont et al, 2018). There is, therefore, an increasing need for a specific in vivo CYP3A7 biomarker.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Among these, Class II cancer genes involved in transcriptional regulation are prevalent. For example, an allele of CYP3A7 is associated with poor outcomes in leukemia, breast and lung cancers 45 . Intriguingly, some of the Class II genes interacting with the CYP3A7-CYP3AP1 cassette, such as SLC19A1 46 , were reported to associate with clinical outcomes.…”
Section: Resultsmentioning
confidence: 99%